RAPPORTS BETWEEN COMPOSITIONAL PARTS OF RURAL AREA IN GJIROKASTRA REGION AND ITS PERSPECTIVES - Sinani, Albina; Duri, Valbona (European Scientific Journal, ESJ, 2014)
Concern about environment is linked with its role in existence of society. Some of the environmental features of our region are: degraded terrains, mainly on the slopes, as the result of deforestations, over use of it for agricultural and livestock purposes, degradation of urban environment especially overcrowded area, reduce of green areas, un controlled interferences in infrastructure, degradation of esthetical elements of landscape etc. For a sustainable economic, socio cultural and ecologic development should be paid importance to the assessment of impact on environment of any kind of activity. The essence of a sustainable development in environment as a unit of co functional elements, outside of which cannot be realised the development of our society. Sustainable development is multifactor and requires the integration of socio economic interest of community, protection of different ecosystems as a value and as an asset, promotion of alternative resources of development, strengthening of people, organizations and other institutions awareness about environment. Providing of environment sustainability of rural area in Gjirokastra region, is a duty that belong to the community, institutions central and local organizations, with the main aim for a sustainable socio economic development.